Behavioral Observations of Ospreys Breeding at Fort Wainwright, Alaska - Ajmi, Amal R. (ARCTIC, 2015)
This study documents observations of breeding behavior at two Osprey Pandion haliaetus carolinensis nest sites discovered at Fort Wainwright, Alaska. We developed Osprey location criteria and behavior and activity classifications from observations in 2006 and 2007, and subsequently measured those behaviors and activities at those locations in 2008–10. Eleven separate observers documented breeding behavior in and around each nest site from 2008 to 2010 for a total of 858 hours. Ground-based behavioral observations by researchers from an enclosed vehicle minimized anthropogenic disturbance. This study provides quantitative and qualitative assessments of breeding behavior that includes incubation, brooding, nest defense, and interloper occurrences from 2008 to 2010 and describes breeding timelines, mean brood size, and productivity from 2006 to 2011. Female Ospreys incubated and brooded significantly more than male Ospreys. Behavioral data suggest that breeding adult females and male Ospreys have differing nest and nest area defensive priorities. Breeding timelines and behaviors documented in this study are similar to those described in the literature. This study provides the first account of breeding phenology and behavior for Ospreys in Interior Alaska. La présente étude fait état de l’observation du comportement reproducteur à deux sites de nidification de balbuzards pêcheurs Pandion haliaetus carolinensis découverts à Fort Wainwright, en Alaska. Nous avons élaboré des critères propres à l’emplacement de même que des classifications relatives aux comportements et aux activités des balbuzards pêcheurs à partir d’observations réalisées en 2006 et en 2007, après quoi nous avons mesuré ces comportements et ces activités à ces mêmes emplacements de 2008 à 2010. Onze observateurs distincts ont pris note des comportements reproducteurs à chaque site et près de chaque site de 2008 à 2010, ce qui a représenté 858 heures d’observation. Les observations du comportement au sol réalisées par les chercheurs à partir d’un ...